2020
DOI: 10.1021/acs.jmedchem.0c00567
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Suprastat: A Novel Selective Histone Deacetylase 6 Inhibitor with the Ability to Potentiate Immunotherapy in Melanoma Models

Abstract: Selective inhibition of histone deacetylase 6 (HDAC6) is being recognized as a therapeutic approach for cancers. In this study, we designed a new HDAC6 inhibitor, named Suprastat, using in silico simulations. X-ray crystallography and molecular dynamics simulations provide strong evidence to support the notion that the aminomethyl and hydroxyl groups in the capping group of Suprastat establish significant hydrogen bond interactions, either direct or water-mediated, with residues D460, N530, and S531, which pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…The long flat cap structure allows the inhibitor to reach more distant portions of L1 and come close to Asp460, a key residue in most recent HDAC6 hydroxamate-based inhibitors, confirming the docking prediction 15 and most recent structural results. 26 Fluorination of benzohydroxamate-based HDAC6 inhibitors has been observed to enhance either their potency 27,28 or their selectivity over HDAC1. 10,15 To clarify the role of fluorination, we prepared and tested the fluorinated analog of ITF3756 (1-FF) and the nonfluorinated analog of ITF3985 (2-H) (see Table 1) against HDAC1 and HDAC6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The long flat cap structure allows the inhibitor to reach more distant portions of L1 and come close to Asp460, a key residue in most recent HDAC6 hydroxamate-based inhibitors, confirming the docking prediction 15 and most recent structural results. 26 Fluorination of benzohydroxamate-based HDAC6 inhibitors has been observed to enhance either their potency 27,28 or their selectivity over HDAC1. 10,15 To clarify the role of fluorination, we prepared and tested the fluorinated analog of ITF3756 (1-FF) and the nonfluorinated analog of ITF3985 (2-H) (see Table 1) against HDAC1 and HDAC6.…”
mentioning
confidence: 99%
“…The tetrazole moiety of the inhibitor exhibits a π–π bond with Phe583 (T-shaped geometry), whereas the pyrimidine moiety shows similar behavior from the thiophenyl substructure in ITF3756, suggesting a π–π bond with the His463 imidazole and a π-alkyl interaction with the Pro464 side chain (L1 pocket). The long flat cap structure allows the inhibitor to reach more distant portions of L1 and come close to Asp460, a key residue in most recent HDAC6 hydroxamate-based inhibitors, confirming the docking prediction and most recent structural results …”
mentioning
confidence: 99%
“…Fourteen-point IC 50 curves were generated using a 3-fold inhibitor dilution series; inhibitor concentration ranges used: 100 μM to 0.063 pM for HDAC1 and HDAC8; and 3 μM to 1.88 pM for HDAC6. Pan-HDACi SAHA was used as a positive control. b The enzymatic data for selective HDAC6i Nexturastat A (NexA) determined under the same conditions were extracted from ref . …”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group has demonstrated that pretreatment with selective HDAC6 inhibitors such as nexturastat A and suprastat before treatment with anti-PD-1-blocking antibodies enhances the therapeutic efficacy of anti-PD-1 checkpoint blockade in melanoma and breast cancer mouse models by downregulating immunosuppressive molecules, decreasing protumoral M2 macrophages, and increasing T cell infiltration [ 98 , 120 , 121 ]. In addition, treating T cells isolated from metastatic melanoma patients with the HDAC6 inhibitors ACY-1215 and ACY-241 decreases Th2-associated cytokines, increases Th1-associated cytokines, decreases FOXP3 expression and T cell exhaustion markers, and increases the accumulation of central memory T cells in the tumors [ 122 ].…”
Section: Epigenetic Modifiers As Therapeutic Adjuvants For Melanoma Patientsmentioning
confidence: 99%